THE PROBLEM OF TERMINOLOGY IN MODERN LINGUISTICS OF UZBEK AND ENGLISH LANGUAGES - Hakimovna, Gafurova Dilbar; Burievich, Sariev Akhtam; Tukhtasinovna, attorova Dilrabo; Sadikovna, Mirxanova Matluba; Romanovna, Sharipova Albina (International Journal of Psychosocial Rehabilitation, 2020)
In the information society, the study of linguistic-terminology in the Uzbek and English languages have changed the traditionally established boundaries of its description and significantly expanded the field of research. The era of qualitatively new scientific achievements (computer and telecommunication technologies) left its imprint, primarily on terminology, as the most rapidly developing layer of the lexical composition of the language, which was significantly influenced by extralinguistic factors. This study is devoted to the description of the state of linguistic terminology in a synchronous aspect and some considerable drawbacks of it need to be aided.